2009
DOI: 10.1007/s11214-009-9583-9
|View full text |Cite
|
Sign up to set email alerts
|

Large Amplitude Oscillations in Prominences

Abstract: Since the first reports of oscillations in prominences in 1930s there have been major theoretical and observational advances to understand the nature of these oscillatory phenomena leading to a whole new field of so called "prominence seismology". There are two types of oscillatory phenomena observed in prominences; "small amplitude oscillations" ( 2-3 km s −1 ) which are quite common and "large amplitude oscillations" (>20 km s −1 ) for which observations are scarce. Large amplitude oscillations have been fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 46 publications
10
93
2
Order By: Relevance
“…The velocity amplitude was about 19 and 14 km s −1 for the lower and upper threads, respectively, significantly larger than that of small-amplitude oscillations (from 0.1 to several kilometers per second) that are apparently ever-present in prominences (Arregui et al 2012). The present observation therefore provides an alternative cause for large-amplitude prominence oscillations (velocity amplitude 20 km s −1 ), which are relatively rare and have been suggested to be triggered by waves and disturbances produced by flares or jets (Tripathi et al 2009). …”
Section: Flux Feedingmentioning
confidence: 66%
“…The velocity amplitude was about 19 and 14 km s −1 for the lower and upper threads, respectively, significantly larger than that of small-amplitude oscillations (from 0.1 to several kilometers per second) that are apparently ever-present in prominences (Arregui et al 2012). The present observation therefore provides an alternative cause for large-amplitude prominence oscillations (velocity amplitude 20 km s −1 ), which are relatively rare and have been suggested to be triggered by waves and disturbances produced by flares or jets (Tripathi et al 2009). …”
Section: Flux Feedingmentioning
confidence: 66%
“…Filament oscillations triggered by Moreton or coronal waves are often of large amplitude (>20 km s −1 ; see the review by Tripathi et al 2009), distinct from commonly observed smallamplitude oscillations (∼2-3 km s −1 ; see the review by Arregui et al 2012), which are usually local and seemingly intrinsic to the filament itself without any obvious trigger. The physical nature of the wave-filament interaction is not well understood as observations are relatively scarce (Ramsey & Smith 1966;Hyder 1966;Eto et al 2002;Okamoto et al 2004;Gilbert et al 2008;Hershaw et al 2011;Liu et al 2012b;Jackiewicz & Balasubramaniam 2013), and a filament does not always oscillate when a wave passes by (Okamoto et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The oscillations are categorised as either large amplitude oscillations, where the entire prominence oscillates with a velocity amplitude of the order of tens of km s −1 and periods ranging from around 6 to 150 min, or small amplitude oscillations which are localised to part of the prominence, and have velocity amplitudes of around 2-3 km s −1 and typical periods of 10 to 80 min. While small amplitude oscillations are very common (see Oliver & Ballester 2002), large amplitude oscillations are less widely reported and there are relatively few observational analyses (see the review by Tripathi et al 2009, their Table 1). …”
Section: Introductionmentioning
confidence: 99%